The Importance of Managing eWOM in the Hotel Industry - Horák, Tomáš; Karlíček, Miroslav, 1979-; Pearce, Chris; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
The goal of this thesis is to investigate the effects of different hotel response strategies to negative user-generated electronic word of mouth on online travel guide sites and subsequently to identify managerial implications that would lead to an effective online review management in the hotel industry. Three basic response strategies to a negative review were identified: no-response strategy, defensive response strategy and accommodating response strategy. An experimental research method with 240 respondents proved that accommodating response to a negative review has positive impact on customer's perception of a hotel. The most negative perception was observed by the defensive response strategy. The results of this experimental research were confirmed in a Mann-Whitney U-test.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses